Monoclonal antibodies against contact sites A of Dictyostelium discoideum: detection of modifications of the glycoprotein in tunicamycin-treated cells - Ochiai, H. (1982)
Tunicamycin acts on cell aggregation in Dictyostelium discoideum by changing cell movement and by inhibiting the EDTA-stable type of intercellular adhesion. Tunicamycin-treated cells show unco-ordinated pseudopodial activity such that pseudopods are simultaneously extended from all parts of the cell surface, and the cells are unable to move in straight paths. Concurrent with the inhibition of formation of EDTA-stable contacts, N-glycosylation of a glycoprotein specific for aggregation-competent cells is inhibited. This glycoprotein, previously called contact site A, has an apparent mol. wt. of 80 kilodaltons (kd). In membranes of tunicamycin-treated cells, two components are detected that react with certain monoclonal antibodies against contact sites A: one component of 66 kd, the other of 53 kd apparent mol. wt. Another group of monoclonal antibodies reacts only with the 80-kd glycoprotein and the 66-kd component. These results are in accord with the assumption that the glycoprotein carries two carbohydrate chains, and that the antibodies differ in their requirement for glycosylation of the antigen. Despite the coincidence between blockage of EDTA-stable cell adhesion and inhibited glycosylation of contact sites A, direct involvement of the carbohydrate moieties of this glycoprotein in intercellular adhesion seems questionable. EDTA-stable cell adhesion has not been blocked by Fab fragments from antibodies that specifically react with the glycosylated protein.